2010
DOI: 10.1042/bc20090161
|View full text |Cite
|
Sign up to set email alerts
|

ESCRT & Co

Abstract: Components of the ESCRT (endosomal sorting complex required for transport) machinery mediate endosomal sorting of ubiquitinated membrane proteins. They are key regulators of biological processes important for cell growth and survival, such as growth-factor-mediated signalling and cytokinesis. In addition, enveloped viruses, such as HIV-1, hijack and utilize the ESCRTs for budding during virus release and infection. Obviously, the ESCRT-facilitated pathways require tight regulation, which is partly mediated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 257 publications
(293 reference statements)
0
47
0
1
Order By: Relevance
“…Previous reports have shown that removal of tsg101 and components that mediate sorting of ubiquitylated transmembrane proteins to late endosomes (Roxrud et al, 2010) within the developing eye imaginal disc result in the activation of Notch pathway signalling and non-autonomous overgrowth of surrounding tissue (Moberg et al, 2005;Vaccari and Bilder, 2005). Strikingly, this non-autonomous overgrowth is mediated by the ectopic expression of Upd, which is a target gene of Notch in the developing eye (Chao et al, 2004;Flaherty et al, 2009).…”
Section: Jak-stat Pathway Signalling Endocytosis and Notchmentioning
confidence: 96%
“…Previous reports have shown that removal of tsg101 and components that mediate sorting of ubiquitylated transmembrane proteins to late endosomes (Roxrud et al, 2010) within the developing eye imaginal disc result in the activation of Notch pathway signalling and non-autonomous overgrowth of surrounding tissue (Moberg et al, 2005;Vaccari and Bilder, 2005). Strikingly, this non-autonomous overgrowth is mediated by the ectopic expression of Upd, which is a target gene of Notch in the developing eye (Chao et al, 2004;Flaherty et al, 2009).…”
Section: Jak-stat Pathway Signalling Endocytosis and Notchmentioning
confidence: 96%
“…ESCRTs consist of approximately twenty proteins that assemble into four complexes (ESCRT-0, -I, -II and -III) with associated proteins (VPS4, VTA1, ALIX), which are conserved from yeast to mammals (Henne et al, 2011;Roxrud et al, 2010). The ESCRT-0 complex recognizes and sequesters ubiquitylated proteins in the endosomal membrane, whereas the ESCRT-I and -II complexes appear to be responsible for membrane deformation into buds with sequestered cargo, and ESCRT-III components subsequently drive vesicle scission (Hurley and Hanson, 2010;Wollert et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The role of ESCRT-II in cytokinesis is unclear, although studies conducted by Langelier et al, 2006 indicate that Vps22 of ESCRT-II is located on the centrosomes and is involved in the maturation of these organelles. The mechanisms behind ESCRT mediated scission and their role in microtubule disassembly have been recently reviewed in detail by Henne et al, 2011 andRoxrud et al, 2010 and will not be further discussed in this review.…”
Section: The Roles Of Escrt Proteins In Healthy Cells and In Disease 459mentioning
confidence: 99%
“…Given their importance in fundamental cellular processes, it is not surprising that ESCRT dysfunction is associated with numerous diseases, including neurodegenerative disorders, cancer and infectious diseases. The dynamics and regulation of the ESCRT machinery have been extensively reviewed (Hurley & Emr, 2006;Saksena et al, 2007;Williams & Urbe, 2007;Raiborg & Stanmark, 2009;Hanson et al, 2009;Roxrud et al, 2010;Henne et al, 2011) and will only be mentioned briefly here. This review focuses on understanding the role of the ESCRTs' in disease using model systems, to better understand the mechanisms behind their role in pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation